Pertanggungjawaban Otorita Ibu Kota Nusantara Dalam Penyelenggaraan Tata Pemerintahan - Nadhir, Nabiyla; Sinaga, David Parlinggoman; Syawal, Muhammad; Patola, Innayah Maghfirah (JURNAL USM LAW REVIEW, 2024)
This research aims to analyze the form of accountability of the Archipelago Capital Authority after the passing of the Archipelago Capital Law. The relocation of the country's capital will be based on social, economic, political and geographical conditions in the region that create new governance dynamics. The existence of structural changes in the implementation and governance of government in the new national capital has given rise to urgency in research related to the accountability mechanism of the Archipelago Capital Authority, which is something new in Indonesian state affairs. Through literature and theoretical studies as well as a doctrinal research approach, it is stated that the Nusantara Capital City Authority functions as a ministry-level institution that administers the Special Regional Government for the Archipelago Capital City. The position of the Archipelago Capital Authority then became an anomaly because the concept of authority was not appropriate for special regional government units. Then the responsibility of the Archipelago Capital Authority is carried out in two dimensions, namely legal and political responsibility. Apart from that, the authority obtained by the Archipelago Capital Authority through the Archipelago Capital Law is an attribution which causes responsibility to lie with the recipient of the authority (attributeary). Penelitian ini bertujuan untuk menganalisis bentuk pertanggunjawaban Otorita Ibu Kota Nusantara pasca disahkannya Undang-Undang Nomor 3 Tahun 2022 tentang Ibu Kota Negara. Pemindahan ibu kota negara dilatarbelakangi atas kondisi social, ekonomi, politik dan geografi wilayah yang menciptakan dinamika tata pemerintahan yang baru. Adanya perubahan struktur dalam pelaksanaan dan tata kelola pemerintahan di ibu kota negara baru menimbulkan urgensi dalam penelitian terkait dengan mekanisme pertanggungjawaban Otorita Ibu Kota Nusantara yang menjadi hal baru dalam ketetanegaraan Indonesia. Melalui kajian pustaka dan teoretik serta dengan pendekatan penelitian doktriner, dinyatakan bahwa Otorita Ibu Kota Nusantara berfungsi sebagai lembaga setingkat kementerian yang menyelenggarakan Pemerintahan Daerah Khusus. Kedudukan Otorita Ibu Kota Nusantara tersebut kemudian menjadi anomali karena konsep otorita tidak tepat dengan satuan pemerintahan daerah yang bersifat khusus. Kemudian pertanggung jawaban Otorita Ibu Kota Nusantara dilaksanakan dalam dua dimensi yaitu pertangggungjawaban hukum dan politik. Selain itu, kewenangan yang didapatkan oleh Otorita Ibu Kota Nusantara melalui Undang-Undang Ibu Kota Negara merupakan atribusi yang menyebabkan pertanggungjawabannya berada pada penerima wewenang (atributaris), atau dalam hal ini adalah Otorita Ibu Kota Nusantara itu sendiri.